A new optical fibre sensor to assess the stability of geogrid-reinforced soil walls. Issue 4 (1st August 2009) - Yoshida, K.; Yashima, A.; Yokota, Y.; Tsuji, S.
Abstract : ABSTRACT: It is not easy to assess the stability of vertical soil walls reinforced by geogrids during and after construction. This paper describes a unique monitoring system called an 'optical fibre sensor geogrid' in which an optical fibre sensor is installed within a longitudinal member of a geogrid reinforcement material. The structure of the optical fibre sensor and the measuring method to record strain in the geogrid are described. Laboratory tests were first carried out to assess the accuracy of geogrid strain measurements using the optical fibre sensor method. Optical fibre sensor geogrids were then used to measure the strain in embedded geogrid layers in three reinforced soil walls constructed in the field. The system allows the stability of reinforced soil walls to be monitored continuously during and after construction, and a stability evaluation index to be assigned to the walls based on peak strain readings.